Does pedicle screw fixation of the subaxial cervical spine provide adequate stabilization in a multilevel vertebral body fracture model? An in vitro biomechanical study. (March 2018) - Duff, John; Hussain, Mir M.; Klocke, Noelle; Harris, Jonathan A.; Yandamuri, Soumya S.; Bobinski, Lukas; Daniel, Roy T.; Bucklen, Brandon S.
Abstract: Background: Cervical vertebral body fractures generally are treated through an anterior-posterior approach. Cervical pedicle screws offer an alternative to circumferential fixation. This biomechanical study quantifies whether cervical pedicle screws alone can restore the stability of a three-column vertebral body fracture, making standard 360° reconstruction unnecessary. Methods: Range of motion (2.0 Nm) in flexion-extension, lateral bending, and axial rotation was tested on 10 cadaveric specimens (five/group) at C2–T1 with a spine kinematics simulator. Specimens were tested for flexibility of intact when a fatigue protocol with instrumentation was used to evaluate construct longevity. For a C4–6 fracture, spines were instrumented with 360° reconstruction (corpectomy spacer + plate + lateral mass screws) (Group 1) or cervical pedicle screw reconstruction (C3 and C7 only) (Group 2). Findings: Results are expressed as percentage of intact (100%). In Group 1, 360° reconstruction resulted in decreased motion during flexion-extension, lateral bending, and axial rotation, to 21.5%, 14.1%, and 48.6%, respectively, following 18, 000 cycles of flexion-extension testing. In Group 2, cervical pedicle screw reconstruction led to reduced motion after cyclic flexion-extension testing, to 38.4%, 12.3%, and 51.1% during flexion-extension, lateral bending, and axial rotation, respectively. Interpretation: The 360° stabilization procedure provided the greatest initial stability. Cervical pedicle screw reconstruction resulted in less change in motion following cyclic loading with less variation from specimen to specimen, possibly caused by loosening of the shorter lateral mass screws. Cervical pedicle screw stabilization may be a viable alternative to 360° reconstruction for restoring multilevel vertebral body fracture. Highlights: Cervical fracture is corrected by 360° fusion using lateral mass screws with corpectomy spacer/plate 360° fusion may be unnecessary as navigational techniques lower complication rates associated with cervical pedicle screws Biomechanical comparisons between 360° fusion (C3 to C7) and pedicle screw reconstruction (C3 and C7 only) are made Surgical constructs significantly reduced intact; no significant differences were observed between constructs